PURIFICATION OF UNDERGROUND WATER USING SORBENT BASED ON SILICONY ROCK-FLASK OF WEST KAZAKHSTAN - Montaev, S. A.; Satayeva, S. S.; Narikov, K. A.; Urazova, A. F.; Sdikova, G. Zh.; Mambetova, M. B.; Nazarova, D. S. (Rasayan Journal of Chemistry, 2022)
Currently, the Republic of Kazakhstan maintains an intense environmental situation that is associated with an anthropogenic impact on water supply sources. Technically, providing the required amount of water is a feasible task, but the supplied water must be of a certain quality and comply with drinking water supply standards. In this regard, it is a necessity today to constantly monitor the quality of underground water sources used to purify them from harmful impurities using the most effective and readily available natural sorbents. The paper presents the results of studies of the physical and chemical properties of groundwater from wells No. 48 belonging to LLP "ESCEIPA" and the village of Dzhangala, West Kazakhstan region. A siliceous rock-a flask of Western Kazakhstan was used as an adsorbent for water purification. Acid activation was carried out to increase the sorption capacity of the flask. Permanganate oxidizability, sulfate ions, and dry residue were determined in the studied water samples before and after treatment, the following. The studies were carried out with the original and modified flask. The experimental data obtained showed that the best results were achieved after acid activation of the sorbent. Thus, the content of mineral salts has decreased by 2 times, the permanganate oxidizability for the "ESCEIPA" water sample is below the permissible concentration, and the content of sulfate ions is close to the technical conditions. It has been proved that it is possible to use a flask for groundwater treatment, and acid modification improves the sorption characteristics of the material under study. В настоящее время в Республике Казахстан сохраняется напряженная экологическая ситуация, связанная с антропогенным воздействием на источники водоснабжения. Технически обеспечить необходимое количество воды – задача выполнимая, но подаваемая вода должна быть определенного качества и соответствовать нормам питьевого водоснабжения. В связи с этим на сегодняшний день необходим постоянный контроль качества подземных вод, используемых для их очистки от вредных примесей с использованием наиболее эффективных и легкодоступных природных сорбентов. В работе представлены результаты исследований физико-химических свойств подземных вод из скважины №48, принадлежащей ТОО «ESCEIPA» и поселка Джангала Западно-Казахстанской области. В качестве адсорбента для очистки воды использовалась кремнистая порода-опока Западного Казахстана. Кислотную активацию проводили для увеличения сорбционной емкости колбы. В исследуемых пробах воды до и после обработки определяли перманганатную окисляемость, сульфат-ионы и сухой остаток. Исследования проводились на оригинальной и модифицированной колбе. Полученные экспериментальные данные показали, что наилучшие результаты достигаются при кислотной активации сорбента. Так, содержание минеральных солей уменьшилось в 2 раза, перманганатная окисляемость для пробы воды «ВСЦЭИПА» ниже допустимой концентрации, а содержание сульфат-ионов близко к техническим условиям. Доказана возможность использования опоки для очистки подземных вод, а кислотная модификация улучшает сорбционные характеристики исследуемого материала
Keywords: скопус; импакт-фактор 2022; scopus; дальнее зарубежье; научный журнал; периодическое издание; очистка воды; активация сорбента